A new species of black fly (Diptera: Simuliidae) with an entirely yellow thorax from Darjeeling, India - Takaoka, Hiroyuki; Thapa, Sachin; Henry, Willie (Zootaxa, 2011)
A new black fly species, Simulium (Nevermannia) subratai sp. nov., is described on the basis of female, pupal and larval specimens collected from Darjeeling, India. This new species is assigned to the feuerborni species-group of the subgenus Simulium (Nevermannia), and is characterized by the entirely yellow female thorax and the larval abdomen without any colored markings. This is the first record of a black fly species with the adult having an entirely yellow thorax in the Oriental Region.